Discussions for the charging efficiency of the resistor–capacitor and resistor–inductor–capacitor series circuits under different excitation sources. (November 2022) - Sun, Dun; Tian, Sheping; Jiao, Xingchao; Jiang, Yuning
Abstract: Aiming at the resistor–capacitor (RC) series circuit and resistor–inductor–capacitor (RLC) series circuit of capacitor charging, this paper discusses the energy efficiency of the capacitor charging circuit under the four excitation conditions of the step function, slope function, quadratic function, and exponential function. The simulation circuits are built based on MATLAB Simulink, and are compared under the four excitation conditions. It is pointed out that the charging efficiency of the RC series circuit and RLC series circuit under slope function excitation can reach the maximum value. Under the same slope function excitation, the energy efficiency of the RC series circuit is almost the same as that of the RLC series circuit, while the charging time of the second-order RLC series circuit is shorter.